2012
DOI: 10.1016/j.diabres.2011.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Durability of glycemic control using U-500 insulin

Abstract: Previous short-term studies evaluating U-500 insulin have reported improvements in glycemic control but with significant weight gain. This study was performed to examine the glycemic durability of U-500 insulin in highly insulin resistant subjects, and to determine if weight gain was continuous with use. Patients using U-500 insulin provided consent for chart reviews for up to 3 years prior to and 3 years after use of U-500 insulin. Charts were reviewed for physical and metabolic data from 53 subjects using U-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…A recent case series reported an increase in mild hypoglycemia from 13.0% prior to U-500R to 42.0% after initiation of U-500R therapy. 27 Some studies have reported more episodes of mild hypoglycemia in the early period after initiation of U-500R; 15 28 however, our analysis did not show any difference between the early and later postindex period ( table 4 ). In the current study, there were no episodes of severe hypoglycemia accompanied by hypoglycemic coma.…”
Section: Discussioncontrasting
confidence: 55%
“…A recent case series reported an increase in mild hypoglycemia from 13.0% prior to U-500R to 42.0% after initiation of U-500R therapy. 27 Some studies have reported more episodes of mild hypoglycemia in the early period after initiation of U-500R; 15 28 however, our analysis did not show any difference between the early and later postindex period ( table 4 ). In the current study, there were no episodes of severe hypoglycemia accompanied by hypoglycemic coma.…”
Section: Discussioncontrasting
confidence: 55%
“…Low-density lipoprotein cholesterol remained unchanged. 28 , 29 , 34 , 52 In Phase III trials, the levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, total cholesterol, and triglycerides values appeared similar between degludec U100 and glargine at 26 weeks and 52 weeks. 53 No clinical effects of glargine U300 on cholesterol are available.…”
Section: Body Of Reviewmentioning
confidence: 94%
“…When compared with baseline, up to 3 years of treatment with U-500R did not affect blood pressure or the number of blood pressure medications prescribed. 28 , 34 When compared with insulin glargine, the treatment with insulin degludec did not affect blood pressure or heart rate. 39 Treatment effects of glargine U300 on blood pressure are not available from the EDITION trials.…”
Section: Body Of Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Once U-100 insulin requirements exceed 200 U daily, transitioning to U-500 insulin can improve long-term glycemic control, be more cost effective, and provide higher patient satisfaction (3)(4)(5). U-500 insulin via continuous subcutaneous administration may provide improvement in glucose control without adverse effects in patients who have failed to achieve it with multiple daily injections (6).…”
Section: Introductionmentioning
confidence: 99%